Silver Nanoparticles - Fabrication, Characterization and Applications 2018
DOI: 10.5772/intechopen.74623
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Antimicrobial Properties of Silver Nanocomposites

Abstract: Nanoparticles and polymers in their respective fields have contributed greatly in the form of science and hence in daily life application products. But due to lack in emerging technologies for developing silver nanocomposites with polymers and other materials, the nanoparticle-based products have conquered little less attention. Hereby, an effort is made to put a light on already developed functional materials containing silver nanoparticles and also to look forward their scope in daily life applications. A li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 52 publications
0
8
0
1
Order By: Relevance
“…Antibacterial activity is usually attributed to electrostatic interactions between cations and the negatively charged membrane surface of bacteria and/or to other interactions between the cations and the bacteria’s RNA/DNA proteins [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. As a result, antibacterial coatings usually contain positively charged materials in the form of either small molecules (mostly metal ions such as copper [ 11 , 12 , 13 , 17 , 19 , 20 , 21 , 22 ], silver [ 17 , 18 , 21 ], zinc [ 21 , 23 , 24 ], cobalt [ 25 ], nickel [ 26 ] or polyoxometalates [ 27 , 28 ]), nanoparticles (such as silver-based nanoparticles [ 15 , 29 , 30 , 31 ], rubidium-silver-titanium oxide nanocomposites [ 32 ], phenol-based nanoparticles [ 33 ] or silica-based nanoparticles [ 31 , 34 , 35 , 36 , 37 ]) or polymeric (such as chitosan/chitin [ 38 , 39 ], modified poly(ethylene imine) [ 40 , 41 , 42 , 43 ], quaternary ammonium containing polymers [ 44 , 45 , 46 ,…”
Section: Introductionmentioning
confidence: 99%
“…Antibacterial activity is usually attributed to electrostatic interactions between cations and the negatively charged membrane surface of bacteria and/or to other interactions between the cations and the bacteria’s RNA/DNA proteins [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. As a result, antibacterial coatings usually contain positively charged materials in the form of either small molecules (mostly metal ions such as copper [ 11 , 12 , 13 , 17 , 19 , 20 , 21 , 22 ], silver [ 17 , 18 , 21 ], zinc [ 21 , 23 , 24 ], cobalt [ 25 ], nickel [ 26 ] or polyoxometalates [ 27 , 28 ]), nanoparticles (such as silver-based nanoparticles [ 15 , 29 , 30 , 31 ], rubidium-silver-titanium oxide nanocomposites [ 32 ], phenol-based nanoparticles [ 33 ] or silica-based nanoparticles [ 31 , 34 , 35 , 36 , 37 ]) or polymeric (such as chitosan/chitin [ 38 , 39 ], modified poly(ethylene imine) [ 40 , 41 , 42 , 43 ], quaternary ammonium containing polymers [ 44 , 45 , 46 ,…”
Section: Introductionmentioning
confidence: 99%
“…Silver ions were also reported to induce reactive oxygen species in bacteria which leads to the destruction of the bacterial cell ( Meena et al, 2013 ; Shaikh et al, 2019 ). It has been reported that the antimicrobial activity of Ag-NPs was enhanced by the combination of polymer even at low concentrations ( Chen et al, 2016 ; Abbas et al, 2018 ; Batista et al, 2018 ). Chitosan, a cationic polysaccharide was used along with Ag-NPs to improve the antimicrobial properties of NPs ( Abdelgawad et al, 2014 ).…”
Section: Role Of Nanotechnology In Crop Protectionmentioning
confidence: 99%
“…Ag-NPs are one of the most promising system to fight the emergence of pathogenic bacterial strains and the increase of resistant microorganisms resulted from the excessive use of antibiotics [67]. Nanotechnology products database 2019 reported, Ag-NCs have been used in 278 different types of product in 34 countries and 15 industries with diverse properties and applications [68,69].…”
Section: Silver Nanoparticlesmentioning
confidence: 99%